Visual search behaviour in skilled field-hockey goalkeepers - Canal-Bruland, R.; van der Kamp, J.; Arkesteijn, M.; Janssen, R. G.; van Kesteren, J.; Savelsberg, G. J. P. (International Journal of Sport Psychology, 2010)
In several sports, effective visual information pick-up has been shown to be crucial for successful goalkeeping. However, most of the studies that used videobased techniques, presented their participants with videos captured from a stationary camera view. In this study, we examined whether visual search behaviour and performance differ when presenting the stimuli with a moving camera view compared to a stationary camera view. To this end, we invited 15 skilled goalkeepers to watch video clips (from either a stationary or a moving camera perspective) of hockey penalty corners on a large screen, and to move a joystick in response to the actions observed. Visual gaze behaviour differed across the viewing conditions. Results suggest that in the moving camera condition visually tracking the ball resulted in visually `overshooting` the stopping location of the ball (i.e., gaze tracking briefly continued beyond that stopping location), thereby leading to performance decrements. In contrast, shifting gaze towards the ball-and-stick location prior to ball release was a more beneficial strategy among skilled hockey goalkeepers.